Pengaruh Tradisi Mappacci Terhadap Kehidupan Sosial dan Keluarga Dalam Adat Bugis - Thahir, Abdullah; Nurhamdiah (CV. Kurnia Grup, 2025)
The Mappacci tradition is one of the most important traditional rituals in Bugis culture, carried out ahead of marriage as a symbol of self-purification and preparation for entering domestic life. This research aims to analyze the symbolic meaning of the elements in the Mappacci tradition as well as the social and cultural values contained in it. With a descriptive qualitative approach and Charles Sanders Peirce's semiotic method, this research was conducted in Bone Regency, South Sulawesi, involving traditional leaders, religious leaders, and local communities. The results of the study show that elements such as pacci leaves, candles, pillows, and silk sarongs in Mappacci have a deep philosophical meaning, reflecting the values of purity, honesty, honor, and the hope of a harmonious domestic life. This study is expected to contribute to the preservation of local culture and the strengthening of traditional values with Islamic characteristics as a moral foundation.